Penciptaan Nilai Kinerja ESG: Efisiensi Tenaga Kerja Dan Produktivitas Karyawan Pada Perusahaan Terbuka Di Indonesia - Nugroho Murti; Adik Novi Tantria (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study aims to examine the value creation mechanisms of Environmental, Social, and Governance (ESG) performance through labor efficiency in the context of publicly listed firms in Indonesia. While prior studies predominantly evaluate the usefulness of ESG based on aggregate financial performance or market-based outcomes, this study focuses on internal corporate channels by analyzing the employee cost ratio (ECR) and employee productivity. Drawing on the Resource-Based View, labor is conceptualized as a strategic resource through which ESG practices can support sustainable value creation. The analysis employs balanced panel data regression using a fixed-effects model to control for unobserved firm-specific heterogeneity and time effects, while incorporating firm-specific control variables. Robustness is assessed using bootstrap resampling with 1,000 resampling. The results show that ESG performance is negatively associated with ECR and positively associated with employee productivity. These findings provide empirical evidence that ESG practices contribute to improvements in firms’ internal operational efficiency through the effective utilization of human resources.